Flumatinib plus venetoclax as an effective therapy for Philadelphia chromosome‐positive acute myeloid leukemia: A case report. Issue 1 (3rd January 2023) - Huang, Si‐Man; Tao, Tao; Wan, Chao‐Ling; Wu, Tian‐Mei; Cao, Han‐Yu; Qiu, Yan; Shen, Xiang‐Dong; Wang, Bin‐Ru; Ge, Shuai‐Shuai; Li, Yan‐Yan; Zhang, Tong‐Tong; Wu, Bing; et al.
Abstract: Philadelphia chromosome‐positive acute myeloid leukemia (Ph + AML) is a rare type of AML with a low survival rate and poor prognosis. We first report a Ph + AML patient who remained in long‐term remission after the combination of flumatinib and venetoclax, which could provide corresponding treatment ideas for clinical practice. Abstract : The figure shows the treatment process of the patient and the dynamic changes in blood cell count during venetoclax and flumatinib. The BCR::ABL1 transcript was negative after two courses of the combination of venetoclax anf flumatinib. No serious adverse events occurred during the treatment, although hematological toxicity was observed.